2008
DOI: 10.1080/08995600701869585
|View full text |Cite
|
Sign up to set email alerts
|

Shipboard Habitability in the U.S. Navy

Abstract: Studies of sailor quality of life (QOL) reveal that shipboard life is one among several work and non-work factors that help explain retention plans and behavior (Schwerin, Kline, Olmsted, & Wilcove, 2006;Wilcove, Schwerin, & Wolosin, 2003). The study of factors affecting satisfaction with shipboard life lacks serious exploration, with most of the research on shipboard habitability being conducted 25 years ago. In the present study, data from the 2002 Navy QOL Survey were analyzed to reveal the facets of shipbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Wilcove et al (2003) used data from the Navy Quality of Life survey to show that satisfaction with shipboard life (to include habitability factors) was associated with personnel intention to reenlist, career continuance plans, and job performance (Wilcove et al, 2009). In 2008, Wilcove and Schwerin (2008) showed that conditions in the berthing compartments and privacy were negatively associated with crew retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilcove et al (2003) used data from the Navy Quality of Life survey to show that satisfaction with shipboard life (to include habitability factors) was associated with personnel intention to reenlist, career continuance plans, and job performance (Wilcove et al, 2009). In 2008, Wilcove and Schwerin (2008) showed that conditions in the berthing compartments and privacy were negatively associated with crew retention.…”
Section: Introductionmentioning
confidence: 99%
“…Research has provided evidence that habitability is associated with aspects of sailor well-being. The U.S. Navy Atlantic Fleet Inspector General (1969) survey of 71 surface ships identified that one of the most serious deficiencies reported by sailors was difficulty in sleeping due to noise, overcrowding, and inadequate bunks, whereas Broedling (1970) reported that poor living conditions decreased sailor desire to stay in the Navy (as cited in Wilcove & Schwerin, 2008, p. 117). Later data from the 2002 Navy Quality of Life survey showed that enlisted sailors were dissatisfied with personnel storage space (69%), room in the berthing compartment (66%), rack space (65%), privacy (63%), mattresses (54%), and the berthing area (52%; Wilcove, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Habitability is one of the domains of the human systems integration process and is an important factor for optimizing human performance and improving system performance (ASTM, 2015). Historically, better habitability has been associated with enhanced crew morale, increased personnel retention, and improved ship's company effectiveness (OPNAV, 2012;Stein, Benel, & Malone, 1983;Wilcove & Schwerin, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ship (surface ship) and boat (submarine) habitability can be a crucial factor in the successful conduct of both commercial operations and the sustainment of combat operations due to the impact that it has on personnel morale, safety, health and comfort, personnel effectiveness and productivity, recruitment and retention [1][2][3]. Yet it is also reported that there is a serious lack of exploration into the factors which affect satisfaction with shipboard life [4]. Whilst there have been some surveys conducted on US Navy Ships [4][5][6][7][8], there appears to be a complete absence of research conducted on whole-of-boat submarine habitability.…”
Section: Introductionmentioning
confidence: 99%